Pengaruh Positive Emotion, Time Availability, dan Money Availability terhadap Impulsive Buying Behavior Konsumen Mahasiswa pada Department Store di Kota Yogyakarta - Ardiyanto, Faizal (Akmenika, 2017)
This research was conducted to examine the influence of positive emotion, time availability,and money availabilty toward impulsive buying behavior both partially andsimultaneously. The respondent of this research are university students who haveexperienced unplanned buying in several department stores at Yogyakarta City. Purposivesampling method was utilized then 102 respondents were chosen. The resultsindicate that positive emotion, time availability, and money avaiability positively andsignificantly influence impulsive buying behavior. The three independent variables asstated above, simultaneously influence impulsive buying behavior also. Finally, as themanagerial implication stated, it can be concluded that understanding consumerscondition related with unplanned buying is important topics in recent years, especiallyin department store.